(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The crux of the present research work was to evaluate the therapeutic potential of Ethanolic leaf extract of Cucumis melo var. agrestis (ELECM)on Ulcerative Colitis in rats. The successful induction of Ulcerative Colitis was done by intra-rectal administration of 500 μl of acetic acid (4% v/v), rats were euthanized on day 8 by cervical dislocation under anesthesia. The pathological parameters such as colon weight, colon antioxidant enzymes (SOD, CAT), lipid peroxidase enzymes (MDA, MPO), inflammatory markers (TNF- α and IL-6), and histopathological aspects were estimated to evaluate the ELECM against the disease control. Sulfasalazine was used as positive control to compare the protective effect of the ELECM. The GC-MS analysis of ELECM confirms the presence of about 12 specific phytochemicals. Induction of ulcerative colitis was evidenced in the control group due to increased colon weight, lipid peroxidase enzymes, and immune markers also by alleviated levels of antioxidant enzymes in the rat colon. However, ELECM treated group almost reversed the effect of the disease control group, above all the histopathological response of the ELECM-treated group against the acetic acid-induced ulcerative colitis was almost the same as that of the control group, indicating the significant protective effect. Our present study suggests that ELECM extract has significant protective activity against acetic acid-induced ulcerative colitis, due to its higher antioxidant, moderate anti-inflammatory, and mild immune-suppressive effects, and the protective action might be due to the presence of active constituents such as flavonoids and total phenols as presented on the GC-MS analysis report.